2016
DOI: 10.1002/nau.23192
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes for transobturator tension‐free vaginal tapes in women with urodynamic mixed urinary incontinence

Abstract: Word Count: 240 words.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…Habibi et al (30) found that the beneficial effects of TVT-O placement on QoL persisted at 12 months and that the QoL measurements were correlated with urgency outcomes. In another study which evaluated the long-term effects of TOT and TVT-O on QoL, 85-87% of patients reported significant improvements in QoL (9,24). In our study, although statistically significant deterioration was observed in QoL scores, the improvement in QoL was maintained in the short-and mid-term after TOT.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Habibi et al (30) found that the beneficial effects of TVT-O placement on QoL persisted at 12 months and that the QoL measurements were correlated with urgency outcomes. In another study which evaluated the long-term effects of TOT and TVT-O on QoL, 85-87% of patients reported significant improvements in QoL (9,24). In our study, although statistically significant deterioration was observed in QoL scores, the improvement in QoL was maintained in the short-and mid-term after TOT.…”
Section: Discussioncontrasting
confidence: 47%
“…Similarly, in our study, the cure rates were determined as 53.8% for UUI and 60.6% for urgency. In two studies evaluating the medium and long term outcomes over three- and nine-year follow-ups, Abdul-Fattah et al reported a reduction in the cures rates of urgency and UUI, being determined as 51.5% and 57.0%, respectively at year 3 and 35% and 41%, respectively at year 9 ( 9 , 24 ). Similar results were obtained from the review of Jain et al ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…More commonly, women with mixed urinary incontinence undergo surgery to resolve the stress urinary incontinence component of their condition. Although some of these women experience resolution of their urgency urinary incontinence, some have ongoing, bothersome symptoms 151 . Treatments aimed at reducing urgency urinary incontinence symptoms that were not effective before surgery should be tried again, especially if after the surgery the symptoms of stress urinary incontinence are reduced or resolved.…”
Section: Invasive Interventionsmentioning
confidence: 99%
“…2 UI is highly prevalent in women and adversely affects every aspect of woman's life i.e., physical, psychological, and social resulting in low self-esteem, embarrassment, and decreased productivity at work place. 3,4 However, as compared to women suffering from SUI, women with MUI are at least two-fold more likely to be worried by the symptoms. 5 Primarily, SUI is most prevalent, but during late adulthood, MUI is an extremely predominant subtype.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%